2003
DOI: 10.1093/nar/gkg279
|View full text |Cite
|
Sign up to set email alerts
|

Conserved sequence elements associated with exon skipping

Abstract: One of the major forms of alternative splicing, which generates multiple mRNA isoforms differing in the precise combinations of their exon sequences, is exon skipping. While in constitutive splicing all exons are included, in the skipped pattern(s) one or more exons are skipped. The regulation of this process is still not well understood; so far, cis- regulatory elements (such as exonic splicing enhancers) were identified in individual cases. We therefore set to investigate the possibility that exon skipping i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 57 publications
(60 reference statements)
2
48
0
1
Order By: Relevance
“…2B). Analysis of the intron sequences flanking this missing exon identified several conserved sequence motifs associated with exon skipping in mammals (45).…”
Section: Identification and Characterization Of Chicken Il-1rn Its Dmentioning
confidence: 99%
“…2B). Analysis of the intron sequences flanking this missing exon identified several conserved sequence motifs associated with exon skipping in mammals (45).…”
Section: Identification and Characterization Of Chicken Il-1rn Its Dmentioning
confidence: 99%
“…1). A recent bioinformatic analysis revealed complementary motifs in introns upstream and downstream of skipped exons, 46 suggesting that base-pairing interactions may contribute to the regulation of exon skipping. This notion is supported by the fact that exon inclusion is inhibited by artificial RNA pairing between introns.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Initially, the prediction of RNA secondary structures suggested that physical competition between potential intra-and inter-intron RNA pairing was involved in the alternative splicing of FGF-R1. 46 Another example comes from the competition of…”
Section: Rna Secondary Structure In Mutually Exclusive Splicingmentioning
confidence: 99%
“…Intronic sequences located immediately upstream of the 3Ј ss or downstream of the 5Ј ss are functionally important in splicing (38,61). These sequences are highly diverse and could be broadly categorized into GϩC-rich and AϩU-rich regions that constitute distinct pentamer motifs (62).…”
mentioning
confidence: 99%